TLR-4 may mediate signaling pathways of Astragalus polysaccharide RAP induced cytokine expression of RAW264.7 cells. (17th February 2016) - Wei, Wei; Xiao, Hai-Tao; Bao, Wan-Rong; Ma, Dik-Lung; Leung, Chung-Hang; Han, Xiao-Qiang; Ko, Chun-Hay; Lau, Clara Bik-San; WONG, Chun-Kwok; Fung, Kwok-Pui; Leung, Ping-Chung; Bian, Zhao-Xiang; et al.
Abstract: Ethnopharmacological relevance: Polysaccharides of Radix Astragali ( Astragalus membranaceus (Fisch) Bge.; Huangqi) are able to induce cytokine production of macrophages and are considered the main active ingredient for the immune-enhancing effect of this commonly used medicinal herb. Aim of study: To investigate the molecular mechanism of immunomodulating activities of a reported Astragalus polysaccharide, RAP, which is a hyperbranched heteroglycan with average molecular weight of 1334 kDa. Materials and methods: The cytokine production of RAW264.7 cells were analyzed by using ELISA assays while cell viability was assessed by MTT method. Western blot analysis was used for determining protein contents of mitogen-activated protein kinases (MAPKs). In addition, the level of IL-6, iNOS, and TNF-α mRNA was determined by RT-PCR. Results: It has been found that RAP itself did not have any cytotoxic effect on mouse mammary carcinoma 4T1 cells, but it significantly enhanced cytotoxicity of the supernatant of RAW264.7cells on 4T1 cells. Furthermore, RAP enhanced the production of NO and cytokines in RAW264.7 cells, and significantly up-regulated gene expressions of TNF-α, IL-6, iNOS. All these bioactivities were blocked by the inhibitor of TLR4 (Toll-like receptor 4), suggesting that TLR4 is a receptor of RAP and mediates its immunomodulating activity. Further analyses demonstrated that RAP rapidly activated TLR4-related MAPKs, including phosphorylated ERK, phosphorylated JNK, and phosphorylated p38, and induced translocation of NF-κB as well as degradation of IκB-α. These results are helpful to better understand the immunomodulating effects of Radix Astragali. Conclusions: RAP may induce cytokine production of RAW264.7 cells through TLR4-mediated activation of MAPKs and NF-κB. Graphical abstract: